Scaling laws governing the NF3 cleaning plasma in a large area reactor - Leu, G. F.; Goury, C.; Modrzynski, P.; Klindworth, M.; Ellert, C. (International Conference on Plasma Surface Engineering, 2013)
An important part of the thin film Silicon PECVD technology for photovoltaic industry is the Flourine based plasma cleaning of the reactor. Precursors like CxFy, SF6, NF3 or even F2 can be used. The present paper investigates scaling laws governing the processes in NF3 plasma in a large area reactor.